Synthesis and evaluation of 2-pyridinylpyrimidines as inhibitors of HIV-1 structural protein assembly - Kožíšek, Milan; Pávová, Marcela; Kräusslich, Hans-Georg (Bioorganic & medicinal chemistry letters, 2016)
In an effort to identify an HIV-1 capsid assembly inhibitor with improved solubility and potency, we synthesized two series of pyrimidine analogues based on our earlier lead compound N-(4-(ethoxycarbonyl)phenyl)-2-(pyridine-4-yl)quinazoline-4-amine. In vitro binding experiments showed that our series of 2-pyridine-4-ylpyrimidines had IC50 values higher than 28μM. Our series of 2-pyridine-3-ylpyrimidines exhibited IC50 values ranging from 3 to 60μM. The congeners with a fluoro substituent introduced at the 4-N-phenyl moiety, along with a methyl at C-6, represent potent HIV capsid assembly inhibitors binding to the C-terminal domain of the capsid protein.
Gesehen am 28.11.2018